2021
DOI: 10.1186/s12711-021-00656-9
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale transcriptome sequencing in broiler chickens to identify candidate genes for breast muscle weight and intramuscular fat content

Abstract: Background In broiler production, breast muscle weight and intramuscular fat (IMF) content are important economic traits. Understanding the genetic mechanisms that underlie these traits is essential to implement effective genetic improvement programs. To date, genome-wide association studies (GWAS) and gene expression analyses have been performed to identify candidate genes for these traits. However, GWAS mainly detect associations at the DNA level, while differential expression analyses usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…For indigenous chicken, meat production, especially BrW, is the cardinal breeding index. In this study, a significant increase in BrW (about 12 g) was found in the IMF selected population, which was consistent with a previous report that a mild correlation was found between chicken IMF and BrW [ 11 ]. Herein, we used this ideal chicken model to investigate genetic markers associated with BrW.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For indigenous chicken, meat production, especially BrW, is the cardinal breeding index. In this study, a significant increase in BrW (about 12 g) was found in the IMF selected population, which was consistent with a previous report that a mild correlation was found between chicken IMF and BrW [ 11 ]. Herein, we used this ideal chicken model to investigate genetic markers associated with BrW.…”
Section: Discussionsupporting
confidence: 93%
“…Significant phenotypic enhancement and a discrete genetic architecture were identified for this selected line in previous reports [ 9 , 10 ]. Given that IMF and BrW are related, BrW could be enhanced significantly along with the selection of high IMF in chicken [ 9 , 11 ]. Therefore, comparison of the original line and the selected line is an excellent means by which to dissect genetic architecture and explore the genes affecting BrW.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RNA purity was determined using a NanoPhotometer ® -Spectrophotometer (IMPLEN Inc., West Lake Village, CA, USA) and RNA integrity and concentration were measured using the RNA Nano 6000 Assay Kit for the Bioanalyzer 2100 system (Agilent Technologies, Santa Clara, CA, USA). RNA-sequencing was performed on an Illumina NovaSeq 6000 S2 (Illumina Inc., San Diego, CA, USA) and 150-bp paired-end reads were generated [ 13 ]. We then performed quality control on the RNA data using tools Trimmomatic (v0.32) and FastQC (v0.11.7), including removal of low-quality reads (read quality < 30).…”
Section: Methodsmentioning
confidence: 99%
“…This technology has been widely used to explore the mechanisms of complex traits, including human diseases [ 5 , 6 , 7 ], plant development or disease resistance [ 8 , 9 ], as well as animal growth and reproductive capacity [ 10 , 11 ] in past years. Similarly, a GWAS has also been applied to the study of chicken development, especially breast muscle development and some significant candidate genes or genomic regions have been identified [ 12 , 13 , 14 ]. Interestingly, genetic variants within the genome significantly associated with breast muscle development appear to be diverse and are often associated with other traits, such as body weight, full evisceration weight, and so on [ 15 ].…”
Section: Introductionmentioning
confidence: 99%